1974
DOI: 10.1128/iai.10.5.1152-1155.1974
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Formation by Rickettsia conori in WI-38, DBS-FRhL-2, L-929, HeLa, and Chicken Embryo Cells

Abstract: Mammalian cells particularly suitable for the study of specialized aspects of rickettsial biology were tested for their ability to support plaque formation by Rickettsia conori. The detection of plaques was substantially influenced by the combination of growth medium and cell type used. Large plaques (2.0 to 3.0 mm in diameter) occurred by 8 days postinfection in WI-38 and DBS-FRhL-2 cells supported by medium 199. Smaller plaques (0.5 to 1.0 mm in diameter) were seen in L-929 and HeLa cells at 8 to 11 days pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…We investigated the ability of a continuous cell line to support plaque formation by Rickettsia tsutsugamushi, since this technique not only would provide a convenient plaquing procedure in urban laboratories, but would constitute a significant technical advance for overseas laboratories situated in remote geographical areas where pathogen-free eggs are not routinely available. Previous work from this laboratory (7) indicated that L-929 cells would support plaque formation by spotted fever group rickettsiae, and other investigators (9) noted that plaque formation occurred in irradiated L-929 cells infected with typhus or spotted fever group rickettsiae. Since R. tsutsugamushi had been reported to grow in irradiated L-929 cell monolayers (10), it seemed reasonable to expect that plaque formation would occur.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…We investigated the ability of a continuous cell line to support plaque formation by Rickettsia tsutsugamushi, since this technique not only would provide a convenient plaquing procedure in urban laboratories, but would constitute a significant technical advance for overseas laboratories situated in remote geographical areas where pathogen-free eggs are not routinely available. Previous work from this laboratory (7) indicated that L-929 cells would support plaque formation by spotted fever group rickettsiae, and other investigators (9) noted that plaque formation occurred in irradiated L-929 cells infected with typhus or spotted fever group rickettsiae. Since R. tsutsugamushi had been reported to grow in irradiated L-929 cell monolayers (10), it seemed reasonable to expect that plaque formation would occur.…”
mentioning
confidence: 77%
“…Plaque formation by rickettsiae, particularly the typhus and spotted fever group organisms, has been described in primary chicken embryo cell cultures (5,8) and in continuous cell lines (2,7,8). In addition, optimum cultural conditions and diluents have been carefully examined with the primary chicken embryo system (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These include arthropod-borne obligate intracellular parasites which are causative agents for debilitating and lethal vascular diseases in the human host, as well as many species which are nonpathogenic to humans (6,19). Spotted fever group rickettsiae, including R. rickettsii, R. conorii, and R. siberica, can be readily enumerated and isolated by plaque formation on a variety of continuous cell lines (3,11,15,20,28). Typhus group and scrub typhus group organisms, however, form indistinct plaques on green monkey kidney (Vero) (3) and irradiated mouse fibroblast (L-929) cell lines (18).…”
mentioning
confidence: 99%
“…R. conorii Malish (egg 12) was prepared as a 20% yolk sac suspension, and the titers were determined by a plaque assay essentially as previously described (31). Mice were infected subcutaneously with 104 PFU of R. conorii Malish, which had been diluted in brain heart infusion, and were later boosted with 105 PFU by the same route.…”
mentioning
confidence: 99%